ARE YOUR IDEAS MANIFESTED AT YOUR STORY? TRANSITVITY ANALYSIS OF STUDENTS’ NARRATIVE TEXT - Yustika Nur Fajriah; Anisa Siti Cahyani (Institut Pendidikan Indonesia Garut, 2019)
Due to the prominence of students’ capacity in manifesting ideas, this study aims to do transitivity analysis on students’ narrative texts. To attain this aim, qualitative embracing case study design was undertaken. The data in this study were taken from six selected narrative texts written by the students. The data were then analyzed using the criteria of transitivity (linguistic features). The result reveals that students have been tried to amuse readers through their stories by using material process and mental process. However, there is an inadequacy in which students are better to learn more about how to make the text lively (through verbal process).